2019
DOI: 10.21608/ejoh.2019.14116.1110
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Genetic Diversity, and Clustering of Common Bean (Phaseolus vulgaris L.) ‎Accessions Based on Seed Yield and Related Traits ‎

Abstract: T WENTY-SEVEN accessions of common bean were evaluated for their performance and genetic diversity based on 11 seed yield and related traits,with the aim to identify diverse accessions with greater performance to exploit the heterotic potential in hybrid combinations between them, with the possibility to obtain superior segregants in subsequent generations.The study was carried out at El-Dalgamon village, Kafr El-Zayyat, El-Gharbiya Governorate, Egypt, during the two successive summer seasons of 2016 and 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Gonçalves et al [33] also observed that these desired traits with a strong correlation are crucial for selection in plant breeding. In agreement with this result, Alghamdi [32] and Ballat and Araby [21] reported a positive and significant association of seed yield with plant height, pods/plant, and branches/plant and with other characters.…”
Section: Genotypic Correlationsupporting
confidence: 80%
See 1 more Smart Citation
“…Gonçalves et al [33] also observed that these desired traits with a strong correlation are crucial for selection in plant breeding. In agreement with this result, Alghamdi [32] and Ballat and Araby [21] reported a positive and significant association of seed yield with plant height, pods/plant, and branches/plant and with other characters.…”
Section: Genotypic Correlationsupporting
confidence: 80%
“…In terms of the present study, the varieties with high plant height produced more branches per plant and a large number of pods per plant, which contributes to a better amount of seed per plant. This result is supported by Al-Ballat and Al-Araby [21] who reported that the height of the plant is positively and significantly correlated with the number of pods per plant and the seed yield per plant. The number of pods / plant showed significant differences between treatments.…”
Section: Plant Height and Branchessupporting
confidence: 64%
“…Common bean (Phaseolus vulgaris L.) is the most consumed vegetable food legume worldwide either as green pods or as dry seeds and helps in improve fertility of the soil by biological N 2 fixation (Singh, 1999 andAl-Ballat andAl-Araby, 2019). In 2019, the global common bean harvested area was 33.1 million ha and produced 28.9 million tons (FAOSTAT, 2019).…”
Section: Introductionmentioning
confidence: 99%